2019
DOI: 10.1142/s0129065718500168
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Brain Networks of Motor Imagery: Time-Varying Causality Analysis of Scalp EEG

Abstract: Motor imagery (MI) requires subjects to visualize the requested motor behaviors, which involves a large-scale network that spans multiple brain areas. The corresponding cortical activity reflected on the scalp is characterized by event-related desynchronization (ERD) and then by event-related synchronization (ERS). However, the network mechanisms that account for the dynamic information processing of MI during the ERD and ERS periods remain unknown. Here, we combined ERD/ERS analysis with the dynamic networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 75 publications
4
74
1
1
Order By: Relevance
“…Although the brain network method has been applied to the study of motor tasks, the problem of selecting an appropriate reference electrode in EEG research has not been solved (Popovych et al, 2016 ; Storti et al, 2016 ; Li et al, 2018b ). Similarly, the problem of the selection of the reference electrode also exists in the motor imagination (MI) that have similar pattern of brain networks with the ME (Zhang et al, 2015 ; Li et al, 2018a , 2019 ). Recently, some studies investigated how different reference choices influence scalp EEG functional connectivity using simulated EEG data (Chella et al, 2016 ; Huang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the brain network method has been applied to the study of motor tasks, the problem of selecting an appropriate reference electrode in EEG research has not been solved (Popovych et al, 2016 ; Storti et al, 2016 ; Li et al, 2018b ). Similarly, the problem of the selection of the reference electrode also exists in the motor imagination (MI) that have similar pattern of brain networks with the ME (Zhang et al, 2015 ; Li et al, 2018a , 2019 ). Recently, some studies investigated how different reference choices influence scalp EEG functional connectivity using simulated EEG data (Chella et al, 2016 ; Huang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we do not find many applications regarding the characterization of temporal and spectral evolution of coupling between brain regions. Such coupling, generally termed functional connectivity, has been demonstrated temporal non-stationarity, spatial inhomogeneities, and spectral structure [38], [68]. It is natural to take into account the measure of time-frequency coupling between all pairs of regions based on wavelet transform, yielding a big data in tensor form with three modes corresponding to temporal course, spectrum, and spatial connectivity topology.…”
Section: Discussionmentioning
confidence: 99%
“…For each subject, the power spectral density (PSD) of each electrode was first estimated using the pWelch at α (8 -13) and β (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). When exploring the group differences, the PSD of the PL, PR, and HC groups were statistically compared by using the non-parametric Wilcoxon rank-sum test, whose p-values were then multiply corrected by the false discovery rate (FDR) under a significance level of 0.05 (p < 0.05).…”
Section: Power Spectral Densitymentioning
confidence: 99%
“…It facilitates the construction of the time-varying networks on each time point, which thus provides the opportunity to estimate the directed flows among concerned brain regions and to capture the dynamic transition related to the movement effectively. For example, based on the ATDF, Li et al have demonstrated the distinct information processing stages related to the P300 [14] and the motor imagery [15], as well.…”
Section: Introductionmentioning
confidence: 99%